Factors Associated with the Incidence of Gastritis Among Students at Universitas Graha Edukasi Makassar - Mustafa, Sri Resky; Toban, Rindani Claurita; Dumgair, Masea M; Azis, Reskiawati; Mustafa, Saharuddin; Eppang, Yudiarsi (Journal Kiara : Nursing and Midwifery, 2025)
Background: Gastritis is an inflammation of the gastric mucosa caused by irritation or infection and commonly affects young adults, including university students. Lifestyle changes, poor sleep quality, and anxiety are considered contributing factors to the incidence of gastritis among students. Objective: To determine the factors associated with the incidence of gastritis among students at Universitas Graha Edukasi Makassar in 2025. Methods: This study employed an analytical design with a cross-sectional approach. A total of 37 respondents were selected using simple random sampling from Nursing and Midwifery undergraduate students. The instruments included a gastritis questionnaire, the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety levels. Data were analyzed using the Chi-Square test with a significance level of 0.05. Results: The prevalence of gastritis was 62.2%. Respondents with good sleep quality accounted for 62.2%, while 37.8% had poor sleep quality. Anxiety levels were categorized as mild (16.2%), moderate (70.3%), and severe (13.5%). A significant relationship was found between sleep quality and gastritis incidence (p = 0.000 < 0.05). However, no significant relationship was found between anxiety and gastritis incidence (p = 0.778 > 0.05).